Metal Powder Atomisation Methods for Modern Manufacturing. Issue 3 (1st July 2019) - Dunkley, John J.
The recent upsurge of interest in manufacturing techniques using metal powders, including additive manufacturing (AM), metal injection moulding (MIM) and hot isostatic pressing (HIP), has made methods for manufacturing alloyed metal powders especially iron-, nickel- and cobalt-based alloys, a topic of much increased importance. Drawing on 45 years of experience in the field, the author reviews the range of methods available for this purpose, their advantages and limitations and likely fields of application.